The Meaningful Tourism Paradigm in Africa and Asia: A Movement for Transformative Practice - Wolfgang Georg Arlt; Kristel Kessler; Stacy von Cranach; I Nengah Subadra (Language Assistance, 2025)
This article introduces the Special Focus topic on the Meaningful Tourism paradigm, analysing its application as a transformative movement across Africa and Asia. Framed by the need for holistic sustainability beyond quantitative growth, the paradigm mandates the alignment of six core stakeholders: visitors, communities, employees, businesses, government, and environment through objective benefits and subjective satisfaction, measured by SMART KPIs. Drawing on multi-case observations from Cameroon to Mongolia, the analysis reveals how this framework addresses entrenched challenges like economic leakage, cultural erosion, and environmental pressure. It positions Meaningful Tourism as a strategic tool enabling destinations to ‘leapfrog’ unsustainable practices, foster inclusive growth, and build resilience. The synthesis concludes that the paradigm’s global adoption signifies a critical shift from a niche initiative to an essential movement for equitable and future-proof tourism.